2015
DOI: 10.4094/chnr.2015.21.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Postpartum Depression with Socio-Demographic and Clinical Characteristics of Preterm Infants and Mothers.

Abstract: This study was conducted to explore relationships of postpartum depression with socio-demographic and clinical characteristics of preterm infants and mothers. Methods: Participants were the mothers of 80 premature infants admitted to neonatal intensive care units. Postpartum depression was measured using the Edinburg Postnatal Depression Scale (EPDS). Clinical characteristics were examined through the medical records. The physiological state for the infants was evaluated using the revised Neurobiologic Risk Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Conserning emotional health status, the average postpartum depression score was 11.02 points, indicating that nearly half of the mothers (n=40, 44%) had postpartum depression with a score of 12 or above. There have been many studies on postpartum depression in mothers of premature infants, one of which found that 30% of mothers were considered to be at risk of postpartum depression at the time of discharge [ 15 ], while another found that 29.7% of mothers were at risk at 4 to 6 weeks postpartum [ 28 ]. Another study found that 86.1% of the subjects were considered to have postpartum depression with a score of 12 or higher at 2 to 3 weeks postpartum, similar to the findings of the present study [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conserning emotional health status, the average postpartum depression score was 11.02 points, indicating that nearly half of the mothers (n=40, 44%) had postpartum depression with a score of 12 or above. There have been many studies on postpartum depression in mothers of premature infants, one of which found that 30% of mothers were considered to be at risk of postpartum depression at the time of discharge [ 15 ], while another found that 29.7% of mothers were at risk at 4 to 6 weeks postpartum [ 28 ]. Another study found that 86.1% of the subjects were considered to have postpartum depression with a score of 12 or higher at 2 to 3 weeks postpartum, similar to the findings of the present study [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 14.8% of women received education on postpartum management during their pregnancies [ 13 ]; therefore, postpartum health care and education are currently insufficient. Additionally, although many studies have been conducted on the mental health of mothers of preterm infants [ 5 , 12 , 14 , 15 ], there have been few studies on the physical health of South Korean mothers during the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…A preterm infant is related to an infant born before 37 weeks of gestation and they may need special care in the neonatal intensive care units (NICUs) [1] . The separation of infants from their mothers and the NICU environment restricts the visual and tactile interactions between mothers and babies causing anxiety in mothers [2] . The hospitalization of a premature baby increases the emotional vulnerability of mothers and therefore increases the stress and anxiety related to the infant [3] .…”
Section: Introductionmentioning
confidence: 99%
“…우리나라의 산후우울 유병률은 산후 기간에 따라 7.5%에 서 최대 44.5%로 차이가 있었다 [13,14]. 특히 미숙아 어머니의 산후우울 유병률은 만삭아 어머니에 비해 더 높다는 보고가 있 으며 [6], 신생아 집중치료실 퇴원 예정 시점에 미숙아 어머니 의 산후우울 비율은 30%에 이르렀다 [15]. 산후우울을 경험하 는 여성은 불안, 피로, 수면장애, 부적절한 감정 등 정서적 어려 움을 겪게 됨으로써 삶의 질 저하를 경험할 수 있다 [16].…”
unclassified
“…산후우울을 경험하 는 여성은 불안, 피로, 수면장애, 부적절한 감정 등 정서적 어려 움을 겪게 됨으로써 삶의 질 저하를 경험할 수 있다 [16]. 미숙아 지금까지 국내에서 수행된 미숙아 어머니와 관련 연구는 주로 양육 스트레스 [3,19], 산후우울 [5,15,20], 모성 역할 발달 …”
unclassified